ЎҚИТУВЧИ КАСБИЙ КОМПЕТЕНТЛИГИНИ РИВОЖЛАНТИРИШДА ИННОВАЦИОН ТАЪЛИМ МУҲИТИНИНГ ЎРНИ - Бердиева, Ҳ.М. (SCIENCE and SOCIETY, 2020)
The article highlights some aspects of the development of teacher’s pedagogical competence in accordance with innovative educational environment.
Keywords: teacher; education; training; method; system; profession; professionalism; competence; innovative environment; retraining; design